Análise da Política de Assistência Social num município de pequeno porte no Ceará sob a ótica dos direitos de cidadania - Rocha, Maria das Graças Fonsêca (2017)
In its preamble, the Federal Constitution of 1988 includes the formation of the rule of law, which lists rights, well-being, equality and justice among the highest values of society; and also citizenship as one of its foundations, referring also to the inclusion of social assistance as the third pillar of social security - the first two are social security and health. In this way, social assistance leaves the field of philanthropy to the level of public policy, causing a change in its public service as citizens of rights. The field of social assistance actions are municipalities, where the user has direct access to programs, projects, services and benefits, as citizens of rights, thus provoking an interest in researching the issue of citizenship for these users. The proposal is to evaluate the social assistance policy in a small municipality in the state of Ceará, Martinópole, seeking to identify if the concept of citizenship for users corresponds to that described in the National Policy of Social Assistance. The research brings as theoretical discussion poverty, social exclusion, citizenship, and related themes, and as methodology content analysis and in-depth evaluation, being used as data collection instrument the semi-structured interview, and as subjects, users and workers of social assistance policy. The results of the survey indicate that the municipality has a large number of people living in poverty and extreme poverty, beneficiaries of social assistance, living in a context characterized by low educational level, low family income and per capita income, presence of children and adolescents in families, and who have little understanding of social assistance as a public policy. The users present a minimal participation in the development of the Social Assistance indicating that in this context a full citizens